Handbook of self and identity - Leary, Mark R.; Tangney, June Price (New York, NY The Guilford Press, a division of Guilford Publications, Inc., 2005)
The self has emerged as a central construct in many domains of behavioral and social science. This state-of-the-science volume brings together an array of leading authorities to provide the first comprehensive review of theory and research in this burgeoning area. Organized into five sections, chapters address the content, structure, and organization of the self processes related to agency, regulation, and self-control self-evaluation and self-related motivation and emotion interpersonal and cultural aspects of self and identity and self-development across evolutionary time and the life span. Also examined are ways that the development of the self sometimes goes awry, resulting in emotional and behavioral problems. Shedding light on a key dimension of human experience, the [ital]Handbook[/ital] is a definitive reference and text.
I. Introduction -- 1. The Self as an Organizing Construct in the Behavioral and Social Sciences / Mark R. Leary and June Price Tangney -- 2. The Self as a Psycho-Social Dynamic Processing System: A Meta-Perspective on a Century of the Self in Psychology / Walter Mischel and Carolyn Morf -- II. Content, Structure, and Organization of the Self -- 3. Organization of Self-Knowledge: Features, Functions, and Flexibility / Carolin J. Showers and Virgil Zeigler-Hill -- 4. Self and Identity as Memory / John F. Kihlstrom, Jennifer S. Beer, and Stanley B. Klein -- 5. The Reflected Self: Creating Yourself as (You Think) Others See You / Dianne Tice and Harry M. Wallace -- 6. Stability and Variability in Self-Concept and Self-Esteem / Michael H. Kernis and Brian M. Goldman -- 7. A Sociological Approach to Self and Identity / Jan E. Stets and Peter J. Burke -- 8. Implicit Self and Identity / Thierry Devos and Mahzarin R. Banaji -- III. Agency, Regulation, and Control -- 9. Self-Awareness / Charles S. Carver -- 10. Self-Regulation and the Executive Function of the Self / Roy F. Baumeister and Kathleen D. Vohs -- 11. Self-Efficacy / James E. Maddux and Jennifer T. Gosselin -- 12. Self-Systems Give Unique Meaning to Self Variables / Carol S. Dweck, E. Tory Higgins, and Heidi Grant-Pillow -- 13. On Assimilating Identities to the Self: A Self-Determination Theory Perspective on Internalization and Integrity within Cultures / Richard M. Ryan and Edward L. Deci -- IV. Evaluation, Motivation, and Emotion -- 14. Self-Evaluation / Abraham Tesser -- 15. Seeking Self-Esteem: Construction, Maintenance, and Protection of Self-Worth / Jennifer Crocker and Lora E. Park -- 16. Freedom versus Fear: On the Defense, Growth, and Expansion of the Self / Tom Pyszczynski, Jeff Greenberg, and Jamie L. Goldenberg -- 17. How Important Is Social Comparison? / Joanne V. Wood and Anne E. Wilson -- 18. Self-Verification: The Search for Coherence / William B. Swann, Jr., Peter J. Rentfrow, and Jennifer S. Guinn -- 19. Self-Relevant Emotions / June Price Tangney -- 20. Individual Differences in Self-Esteem: A Review and Theoretical Integration / Mark R. Leary and Geoff MacDonald -- V. Interpersonal Aspects of the Self -- 21. The Relation of Self to Social Perception / David Dunning -- 22. Self and Close Relationships / Arthur Aron -- 23. Social Identity / Michael A. Hogg -- 24. Optimal Distinctiveness, Social Identity, and the Self / Marilyn Brewer -- 25. Self Presentation / Barry Schlenker -- 26. Interpersonal Self-Regulation: Lessons from the Study of Narcissism / Frederick Rhodewalt and Deborah Sorrow -- 27. Cultural Models of the Self / Susan E. Cross and Jonathan Gore -- VI. Phylogenetic and Ontological Development -- 28. Subjectivity and Self-Recognition in Animals / Robert W. Mitchell -- 29. Evolution of the Symbolic Self: Issues and Prospects / Constantine Sedikides and John J. Skowronski -- 30. The Development of Self-Representations during Childhood and Adolescence / Susan Harter -- 31. Disturbances of Self and Identity in Personality Disorders / Drew Westen and Amy Kegley Heim -- VII. Epilogue -- 32. The Next Generation of Self Research / June Price Tangney and Mark R. Leary.
Includes bibliographical references and indexes.
Keywords: Self; Identity (Psychology)